Deteksi Kualitatif Boraks pada Jajanan Cimol di Lingkungan Pendidikan Kecamatan Panyileukan - Muhammad Ibnu Salim; Mae Amelianawati; Ratna Sari Listyaningrum (Ma'soem University, 2026)
Snacks, commonly referred to as street foods or light foods, are an integral part of daily dietary habits and are inseparable from community life. One widely consumed and affordable example is cimol, a popular Indonesian fried tapioca ball snack. This study aimed to detect the presence of borax in cimol sold within educational areas across Panyileukan District, Bandung. The research employed descriptive analysis and qualitative testing methods, including flame test, turmeric paper test, and AgNO? precipitation test. These procedures are simple and commonly used for the qualitative detection of borax in food products. Based on examinations of 10 cimol samples collected from various school areas, only one sample tested positive for borax. These findings indicate that most cimol products available in educational zones within Panyileukan District are relatively safe for consumption; however, the detection of borax in one sample suggests that food safety monitoring must continue to be reinforced.